Predictors of Body Mass Index and Maximum Handgrip Strength in 18-21 Year-Old on Remand Detainees on Entry into a South African Correctional Facility - Theron, Marieke; Artz, Lillian; Nel, Johanna H.; Senekal, Marjanne (Child & youth services, 2023)
This study investigated the malnutrition profile of young males (n = 67) and females (n = 52) on remand detainees at entry into a correctional facility and determined clinically important predictors of body mass index (BMI) and maximum handgrip strength (MHGS). Measures included weight, height, triceps skinfold (TS) and maximum handgrip strength (MHGS), socio-demographics food security, meal pattern, food choices, understanding of healthy eating, physical activity, risk-taking behaviors, and presence of symptoms of depression/anxiety. Multiple regression analysis was used to identify significant predictors of body mass index (BMI) and MHGS, which were assessed for clinical importance using novel criteria. Fifteen percent of male and 18% of female detainees were underweight, whereas, 17.3% of female detainees were overweight and 5.8% were obese. None of the males were overweight. Consolidation of results on the clinically important predictors of malnutrition for both male and female detainees led to the identification of four broad areas for intervention, including prevention of risk-taking behaviors, education on healthy eating, alleviation of food insecurity, and lastly prevention and treatment of depression/anxiety. We conclude that undernutrition is the most prominent malnutrition problem evident among young male and female detainees at entry into a correctional facility in the Western Cape, South Africa. Consideration of identified predictors is recommended for future intervention development.